2018
DOI: 10.2166/wst.2018.205
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process conditions for preparation of activated carbon from waste Salix psammophila and its adsorption behavior on fluoroquinolone antibiotics

Abstract: Salix psammophila (SP), a solid waste abundantly available, was applied as a precursor to prepare the activated carbon by chemical activation method using phosphoric acid (HPO). Response surface methodology based on Box-Behnken design was used to optimize the prepared conditions of activated carbon. The effects of concentration of HPO, activation temperature and activation time on the adsorption performance (expressed by the adsorption capacity of ciprofloxacin hydrochloride (CIP) and norfloxacin (NOR)) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As the reaction continued, the C-O groups on catechol and hydroquinone were oxidized to generate C]O. 8 The reaction formulas are shown in eqn (3)- (5). Therefore, the C-C content of nAg-mN-TiO 2 -AC was lowest.…”
Section: Surface Functional Group Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As the reaction continued, the C-O groups on catechol and hydroquinone were oxidized to generate C]O. 8 The reaction formulas are shown in eqn (3)- (5). Therefore, the C-C content of nAg-mN-TiO 2 -AC was lowest.…”
Section: Surface Functional Group Analysismentioning
confidence: 99%
“… 4 Because of its allometric characteristics, it must be cut down at intervals of 3 to 5 years. 5 Therefore, the available SP resources are great. Preparation of AC using SP as a raw material is a promising process for improving SP utilization and decreasing the cost of AC.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon as one of the significant commercial adsorbents has not been studied for the removal of GMF. However, carbonaceous adsorbents of different origins have been used for the adsorption of other fluoroquinolone antibiotics; for example, the use of biochar‐derived porous carbon sheets for the exceptional adsorption of levofloxacin, 12 an amine‐functionalized bamboo‐based magnetic activated carbon for the adsorption of ciprofloxacin and norfloxacin in both batch and fixed‐bed modes, 13 and Salix psammophila‐based activated carbon for the adsorption of norfloxacin 14 . Ding et al showed that activated carbon removed fluoroquinolones more effectively than ozone and biological treatment such as membrane bioreactor, anaerobic‐anoxic‐oxic, and biofilter 15 …”
Section: Introductionmentioning
confidence: 99%
“…Salix psammophila (SPP) is a renewable resource in nature, which can grow in saline-alkali land, has the characteristics of strong regeneration and wide source, and has been paid attention by most researchers (Liu et al 2018;Hao & Li 2019). There are cellulose and lignin in SPP, and hydroxyl group is the main active ingredient.…”
Section: Introductionmentioning
confidence: 99%